2014
DOI: 10.1111/sms.12191
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound characteristics of the patellar and quadriceps tendons among young elite athletes

Abstract: Tendons adapt in response to sports-specific loading, but sometimes develop tendinopathy. If the presence of ultrasound changes like hypoechoic areas and neovascularization in asymptomatic tendons precede (and predict) future tendon problems is unknown. The aim of this prospective cohort study was to investigate the relationship between the development of ultrasound changes in the patellar and quadriceps tendons and symptoms of jumper's knee, as well to examine the medium-term effects of intensive training on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
110
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 39 publications
8
110
2
3
Order By: Relevance
“…Patellar tendon ultrasonography is commonly performed in the routine management of athletes of different disciplines to investigate tendon abnormalities that may occur due to repetitive tendon overload [7][8][9][10] . In fact, patellar tendinopathy is a common overuse disorder typically occurring in athletes who participate in sports that require jumping, including volleyball and basketball, hence the label "jumper's knee" 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Patellar tendon ultrasonography is commonly performed in the routine management of athletes of different disciplines to investigate tendon abnormalities that may occur due to repetitive tendon overload [7][8][9][10] . In fact, patellar tendinopathy is a common overuse disorder typically occurring in athletes who participate in sports that require jumping, including volleyball and basketball, hence the label "jumper's knee" 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound imaging of the patellar tendon is commonly employed to study tendon abnormalities that could occur because of repetitive overload, which is a common happening in professional athletes of various disciplines [10][11][12][13]. Patellar tendinopathy (PT) is especially common in athletes that play sports that require jumping, such as basketball and volleyball, giving it its common-term name of "jumper's knee" [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they also conducted a morphological analysis and found that the athletes with PT had a larger painful tendon compared with the contralateral non-painful side (thickness: 6.9 ± 1.8 mm vs. 4.6 ± 0.6 mm, respectively), whereas the controls had no difference between sides (5.6 ± 1.2 mm vs. 5.3 ± 1.0 mm). Morphological abnormalities in the tendon ultrasound image, such as increased tendon thickness, neovascularization, and presence of hypoechoic areas, have also been found in a large percentage of asymptomatic athletes [9,11,13,22]. Recently, Giacchino et al [23] also conducted a study of patellar tendon size and structure in throwers and found that the prevalence of subclinical tendinopathy was high in the non-dominant patellar tendon as a possible result of the repeated non-dominant lower limb overload.…”
Section: Introductionmentioning
confidence: 99%
“…Otra posibilidad es que este dolor provenga de tejido no tendinoso como la articulación femoro-patelar o alguna otra estructura que de dolor referido al tendón rotuliano en cuyo caso se debe realizar un diagnóstico diferencial. Áreas hipoecoicas representan un factor de riesgo a la hora de desarrollar una tendinopatía rotuliana pero estos cambios estructurales no tienen que estar necesariamente asociados a los síntomas 191 .…”
Section: • Presentación Clínicaunclassified
“…Este mismo autor afirmó que el grosor estaba relacionado con el grado de afectación de las imágenes principalmente en los hombres, donde los tendones cuyas imágenes tenían una anormalidad difusa, desestructurada, eran sobre 44% más gruesos de lo normal y los tendones cuyas imágenes tenían focos anecoicos eran sobre 82% más gruesos de lo normal. Otro autor que estudió jugadores de voleibol adolescentes consideró que el punto de corte para los hombres a partir del cual tenían más posibilidad de generar tendinopatía en el futuro era de 5mm en la zona más proximal del tendón patelar, 4.6mm en la zona media y 4.4mm en la zona mas distal mientras para las mujeres los valores eran de 4.2mm, 4mm y 4.1mm respectivamente 191 . Por otra parte, este aumento de diámetro suele ir asociado con mayor dolor en atletas con tendinopatía 188,194 y puede implicar un cambio inicial en cuanto a la estructura del tendón 94,193 .…”
Section: • Presentación Clínicaunclassified